ANALISIS KESUKSESAN PENERAPAN SISTEM INFORMASI TATA PERSURATAN DINAS DAN KEARSIPAN (TPDK) DEPARTEMEN ENERGI DAN SUMBER DAYA MINERAL DENGAN MENGGUNAKAN MODEL DELONE DAN MCLEAN - , Doney Kusuma, ST.; , Jogiyanto Hartdno M., Prof. Dr., M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Archive information systems developed very quickly and is always an improvement to increase efficiency and effectiveness in government. Improved quality of information systems and quality of information systems are absolutely necessary for improving the quality of human resources, which ultimately resulted in net profits for the ministry in particular and society in general. To development, measures of success of archival information systems that exist today should continue to be done. This research was conducted at the Ministry of Energy and Mineral Resources as a government agency's secondlargest foreign exchange earner for the country, which has quite a lot and spread the archive to be managed properly. This research uses of information systems success model of DeLone and McLean (D & M IS Success Model). Reliability and validity of the model were tested using Structural Equation Modeling (SEM) with the technique of Partial Least Square (PLS).